(untitled) (Journal Intellectual Sufism Research (JISR), 2023)
Ethno-STEM science learning integrates local wisdom into science materials and is taught using the STEM approach. This research is a process of activities to produce valid learning tools. The learning tools developed in this study are lesson plans (RPP), Student Activity Sheets (LKPD), and student creative thinking skills test sheets. This research focused on the validation test (construct and content as well) and the response test of junior high school students. The data collection technique used was a questionnaire. The instruments used in this study were a validation questionnaire and a student response questionnaire. The validators in this study were two people, namely content experts and learning media experts with a background in science education. The final result of this research is to produce ethno-STEM-based science learning tool development products with valid to very valid categories, and student responses related to the learning tools provided show the highest percentage in the good to excellent category.